2020
DOI: 10.1002/dad2.12016
|View full text |Cite
|
Sign up to set email alerts
|

In vivo network models identify sex differences in the spread of tau pathology across the brain

Abstract: Introduction We examined networks of tau connectivity between brain regions based on correlations of their [18F]flortaucipir positron emission tomography (PET) uptake to evaluate sex‐specific differences in brain‐wide tau propagation. Methods PET data of clinically normal and mild cognitive impairment (MCI) subjects from the Alzheimer's Disease Neuroimaging Initiative (ADNI) were used to examine differences in network architectures across the groups. Results The tau‐based network architecture resembled progres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 51 publications
0
31
0
Order By: Relevance
“…Women might have faster cognitive decline than men because of differences in sex hormones, structural brain development, genetics, psychosocial factors, lifestyle factors, functional connectivity, and tau pathology. 45 , 46 , 47 Women might have greater burden of small vessel disease, including white matter hyperintensity volume, and less axonal structural integrity that in turn leads to faster cognitive decline particularly in executive function and processing speed. 48 , 49 Women also appear to have lower gray matter volume, 50 so they might be more vulnerable to both the accelerated gray volume loss that occurs with aging and the differential volume loss in specific brain regions that occurs with neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Women might have faster cognitive decline than men because of differences in sex hormones, structural brain development, genetics, psychosocial factors, lifestyle factors, functional connectivity, and tau pathology. 45 , 46 , 47 Women might have greater burden of small vessel disease, including white matter hyperintensity volume, and less axonal structural integrity that in turn leads to faster cognitive decline particularly in executive function and processing speed. 48 , 49 Women also appear to have lower gray matter volume, 50 so they might be more vulnerable to both the accelerated gray volume loss that occurs with aging and the differential volume loss in specific brain regions that occurs with neurodegenerative diseases.…”
Section: Discussionmentioning
confidence: 99%
“… 101 Third, tau pathologies may spread more in women than in men, particularly in MCI patients. 102 Our App NL-G-F rat model may be highly useful in studying sex differences in AD and their underlying mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…At autopsy, this sex advantage was observed at the earlier Braak stages I/II and III/IV, but no sex differences in verbal memory were observed at late stages V/VI. Interestingly, sex‐specific differences in tau propagation across the brain were observed using tau‐PET to construct tau connectivity networks 132 . The most striking difference was that widespread tau PET uptake increased from CU to MCI to a much greater extent in women than men.…”
Section: Beyond At(n): Other Influences On Disease Progressionmentioning
confidence: 99%
“…CN, cognitively unimpaired; hemi., hemisphere; MCI, mild cognitive impairment; PET, positron emission tomography; SUVR, standardized uptake value ratio. Reproduced with permission from Shohouki et al132 AD as a metabolic disease, a recent study investigated how these factors affect associations between AT(N) biomarkers (CSF Aβ42, CSF p-tau181, FDG PET) and metabolites 135. From 139 blood metabolites tested, the study identified and replicated 8 homogeneous (the same between sexes), 15 heterogeneous (differed by sex), and 3 sex-specific interactions with AT(N) biomarkers (FigureS18in supporting information).…”
mentioning
confidence: 99%